Kyrgyz Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
Performance of the banking sector during the crisis and challenges are discussed. The impact of the political crisis on the banking sector is outlined. The Kyrgyz Republic is one of the most open economies in the world. Gross international reserves (GIR) in the Kyrgyz Republic have increased more than sixfold in the last decade. Gold exports, remittances, and official development assistance have become important sources of reserve accumulation. The current level of reserves in the Kyrgyz Republic comfortably meets most reserve adequacy indicators, but fails on one metric used for low-income countries (LICs).